2009
DOI: 10.1007/s10508-009-9498-2
|View full text |Cite
|
Sign up to set email alerts
|

Latina Mother–Daughter Dyads: Relations Between Attachment and Sexual Behavior Under the Influence of Alcohol or Drugs

Abstract: Associations among mother-daughter attachment, mother and daughter substance abuse, and daughter's sexual behavior under the influence of drugs and alcohol were investigated among 158 adult U.S. Latina daughters. Latina daughters were sampled from four mother-daughter dyad types: substance abusing mother and daughter, substance abusing mother only, substance abusing daughter only, and nonsubstance-abusing mother and daughter. Substance abusing daughters with substance abusing mothers, and daughters who were le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 48 publications
1
22
0
Order By: Relevance
“…For instance, Marianismo , prescribes that the appropriate behavior of Latino women are expected to be submissive, selfless, dependent, and accept the primary responsibility of taking care of the children, spouse and household [48, 49]. Although marianismo is often questioned by some younger Latinas born in the U.S., it generally remains an important component of Latino cultural expectations [50]…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Marianismo , prescribes that the appropriate behavior of Latino women are expected to be submissive, selfless, dependent, and accept the primary responsibility of taking care of the children, spouse and household [48, 49]. Although marianismo is often questioned by some younger Latinas born in the U.S., it generally remains an important component of Latino cultural expectations [50]…”
Section: Discussionmentioning
confidence: 99%
“…Exclusion criteria included enrollment in a drug treatment program during the 12 months prior to the interview. A detailed description of the sample selection criteria and sampling methods is provided elsewhere (20, 21). …”
Section: Methodsmentioning
confidence: 99%
“…Latina mother-daughter dyadic attachment often forges strong lifelong ties in which both dyad-members rely profoundly on one another for emotional, financial, and other support over the lifespan (19). De La Rosa, Dillon, Rojas, Schwartz, and Duan (20) demonstrated that closer attachment to the mother was associated with a daughter's lower engagement in sexual activity while under the influence of drugs, suggesting that daughter's attachment to her mother is protective against this sexual risk behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Thirdly, a notable aspect of the studies reviewed is the over-representation of mothers, the fathers' presence being scarce or even non-existent (e.g., Branstetter, Furman & Cottrell, 2009;Brook et al, 1998;De la Rosa, Dillon, Rojas, Schwartz & Duan, 2010;Foshee & Bauman, 1994;Scragg et al, 2009). This aspect may constitute a bias, since the attachment style, as pointed out by Ravitz, Maunder, Hunter, Sthankiya, & Lancee (2010), may vary within the same family from mother to father, and therefore relate in different ways to drug use.…”
Section: Attachment Figuresmentioning
confidence: 99%
“…More recent work, such as that of De la Rosa et al (2010), indicates that attachment to non-user mothers reduces the risk of daughters' performing maladaptive behaviors (drug use and unsafe sex), whilst attachment to drug-user mothers significantly increases the likelihood that their daughters will have sex under the influence of alcohol. Other studies, however, such as that of Scragg et al (2008), confirmed that low parental attachment is associated with higher risk of smoking among adolescents, regardless of whether the parents smoke or not.…”
Section: Inclusion Of Third Variables In the Relation Between Attachmmentioning
confidence: 99%